2015
DOI: 10.5455/msm.2015.27.429-433
|View full text |Cite
|
Sign up to set email alerts
|

Team Attitude Evaluation: an Evaluation in Hospital Committees

Abstract: Introduction:Patients’ health and safety is not only a function of complex treatments and advanced therapeutic technologies but also a function of a degree based on which health care professionals fulfill their duties effectively as a team. The aim of this study was to determine the attitude of hospital committee members about teamwork in Kerman hospitals.Methodology:This study was conducted in 2014 on 171 members of clinical teams and committees of four educational hospitals in Kerman University of Medical Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…The findings revealed a moderate to high level of attitudes towards teamwork that indicates a positive attitude among critical care nurses in Saudi Arabia. The results are similar to previous studies of clinical teams in Iran and nurses and surgeons in Scotland [ 21 , 22 ]. Several studies revealed that teamwork among nurses improves the patient’s health outcomes, team communication, responsiveness to adverse events, healthcare staff and patient satisfaction, and decreases medical errors [ 13 , 23 , 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…The findings revealed a moderate to high level of attitudes towards teamwork that indicates a positive attitude among critical care nurses in Saudi Arabia. The results are similar to previous studies of clinical teams in Iran and nurses and surgeons in Scotland [ 21 , 22 ]. Several studies revealed that teamwork among nurses improves the patient’s health outcomes, team communication, responsiveness to adverse events, healthcare staff and patient satisfaction, and decreases medical errors [ 13 , 23 , 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…The increasing complexity of the patient population and health-care systems demands fine-tuned collaboration among health-care professionals (Clark, Congdon, Macmillan, Gonzales, & Guerra, 2015). To decrease errors, health-care professionals must be educated in strategies that improve information exchange (Hekmat et al, 2015) A health-care team is defined as two or more individuals who have specialized knowledge and specific roles, make decisions, perform interdependent tasks, and share a common goal such as safe patient care (Wen & Schulman, 2014). The AHRQ, in collaboration with the Department of Defense, developed Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) as the national standard for team training in health care (AHRQ, 2014).…”
mentioning
confidence: 99%
“…Efforts to reduce the incidence of medical errors in the health-care setting have included research funding for safety initiatives, public reporting of data, and use of technology (Godlock et al, 2017). The Hospital Readmission Reduction Program (HRPP) links payments to the quality of health care by reducing payments to hospitals with excess readmissions (Hekmat, Dehnavieh, Rahimisadegh, Kohpeima, & Jahromi, 2015).…”
mentioning
confidence: 99%
“…The development of higher-order skills is especially important in work environments such as healthcare that are considered high-risk because poor skills in critical thinking, communication, and teamwork cause 65% to 80% of preventable errors (Dinh et al, 2021 ; Flin & O’Connor, 2017 ; Hekmat et al, 2015 ; Kossaify et al, 2017 ). An effective strategy for reducing preventable errors is to train students with higher-order skills (Hughes et al, 2016 ; Weaver et al, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, a majority of managers believe college graduates need to be better prepared in these essential skills (National Association of Colleges and Employers, 2019 ). The ability to work as part of a team is critical in high-risk, high workload fields such as healthcare (Dinh et al, 2021 ; Flin & O’Connor, 2017 ; Hekmat et al, 2015 ; Kossaify et al, 2017 ; Poulin & Straut, 2016 ).…”
Section: Introductionmentioning
confidence: 99%